Medicinal plants for diabetes treatment during pregnancy - Volpato, Gustavo Tadeu [UNESP]; Moraes-Souza, Rafaianne Queiroz [UNESP]; Soares, Thaigra Sousa [UNESP]; Leal-Silva, Thais; Damasceno, Débora Cristina [UNESP] (Bentham Science Publishers, 2017)
Diabetes mellitus is a syndrome of great importance that affects an increasing number of people every day. In particular, diabetes is a common and important disease during pregnancy and is marked by complications, both fetal and maternal, that increase the risks of morbidity and mortality for diabetic pregnant women and their offspring. Drugs such as insulin and hypoglycemic drugs are given to treat diabetes, but regular exercise and adequate diet have also been indicated. Furthermore, coadjutant therapies such as medicinal plants are popularly used to reduce diabetes-induced hyperglycemia, either within or outside the context of pregnancy. However, studies examining plant use for diabetes treatment are necessary to confirm its possible effects and its safety for the mother and fetus. The objective of this literature review was to conduct a survey of plant species that are utilized worldwide and their stated therapeutic uses. A literature search was performed using the terms diabetes and pregnancy, which resulted in the identification of 31,272 articles. Of these studies, only 12 (0.0038%) were related to medicinal plants, demonstrating that there has been little investigation into this issue. Of the papers analyzed in this review, half evaluated plant leaves, indicating that these scientific studies attempted to reproduce the preparations commonly used by various populations, i.e., in the form of tea. Additionally, more than 90% of studies utilized experimental animals to evaluate the maternal-fetal safety of medicinal plant substances that may potentially be dangerous for humans. Thus, once confidence levels for plant-derived substances are established based on toxicological analyses and safety is confirmed, it is possible that plants will be used to complement conventional diabetes therapies.
Keywords: Diabetes mellitus; Herbs; Medicinal plants; Pregnancy; Review; Treatment